THE EFFECTS OF PRESHOCK ON THE SUBSEQUENT ACQUISITION AND EXTINCTION OF AN AVOIDANCE RESPONSE IN RATS - De Toledo, Leyla (My University, 1963)
The four interrelated experiments reported in this thesis were designed to study the effects of previous exposure to electric shock on the subsequent conditioning and extinction of an avoidance response in rats. The purposes of the research were twofold. The first objective was to test a conflict hypothesis concerning lengthy avoidance conditioning situations. The second purpose was to investigate the ways in which preshocks used to produce such a state of conflict affected behavior. The results indicated that preshocks have an effect on subsequent avoidance conditioning only when they are paired with stimuli which occur in the avoidance situation. Certain preshock procedures which were supposed to produce conflict did in fact retard acquisition. Furthermore, response possibilities available at the time of preshocks were found to be important determinants of subsequent behavior.
Keywords: conditioning; avoidance response; electric shock; rats; preshock